Letter from G.M. Pettit to James Curtis Booth May 30th, 1853 - Pettit, G. M. (1853)
Concerns appointments to certain posts at the United States Mint.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States